Predicting young drivers' safe behaviour of stopping in the dilemma zone. (January 2023) - Pagomenos, Alexis; Rodwell, David; Larue, Grégoire S.
Highlights: Investigated young driver stopping behaviour in the dilemma zone. Extended Theory of Planned Behaviour with Prototype Willingness Model constructs. Intentions predicted young drivers self-reported safe driving behaviour. Social-reaction pathway constructs increased predictive ability for safe behaviours. Abstract: Young drivers are overrepresented in road crashes, half of which occur at intersections in urban areas. One area of focus for crashes at intersections is the dilemma zone, when a driver approaches a signalised intersection at the onset of the yellow light and is unsure whether to continue through or to stop. A challenge in this area of research has been the lack of focus on safe, rather than risky, driving behaviours of young drivers at intersections and a paucity of research on psychosocial factors that motivate driving decisions at intersections. This study aimed to explain young drivers' intentions and predict their self-reported behaviour of stopping in the dilemma zone (the safe behaviour), using psychosocial factors which influence behaviour in young drivers. Participants were N = 180 young drivers from Queensland. An initial online survey presented three unique scenarios to participants: a general dilemma zone situation, the dilemma zone whilst running late and the dilemma zone where the vehicle in front drives through the yellow light. Participants responded to items measuring Theory of Planned Behaviour (TPB) constructs extended with prototype perceptions and willingness constructs from the Prototype Willingness Model (PWM). A follow-up online survey measured participants' self-reported driving behaviours in the previous three weeks, in each scenario. Hierarchical multiple regressions found that the TPB and PWM constructs significantly explained between 59.1 % and 72.7 % of the variance in intentions to stop. This suggested the utility of extending the TPB with a social-reaction decision making model such as the PWM. The follow-up survey ( N = 74), found that intentions, but not PBC or willingness, significantly predicted 29 % of the variance in young drivers' self-reported stopping behaviour for the general scenario and the running late scenario and 10.8 % for the vehicle in front scenario. The findings of this study suggest the value of researching young drivers' safe behaviours and provide information on psychosocial factors, such as prototype perceptions, that road safety interventions can target in order to reduce road crashes. Additionally, these findings provide evidence for the use of the PWM to extend the TPB, and in investigating young drivers' decisions in the dilemma zone.